Church and state in the ecclesiology of Isaac Thomas Hecker - Miakshin Vasilii (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is dedicated to the ecclesiology of Isaac Thomas Hecker (1819-1888), one of the most prominent and influential American Catholic thinkers of the 19th century. The author deals with Hecker’s understanding of the mutual relationship between Church and state, trying to comprehend his vision of the Church developing under conditions of American democracy. Much attention is paid to the comparison of Hecker’s ideas with the ideas of his contemporaries, eminent American and European church figures, especially Pope Leo XIII. Meanwhile, within the limits of the article the author describes Hecker’s views in a rather schematic way, covering just one aspect of his ecclesiology without mentioning controversy over Americanism and the encyclical Testem Benevolentiae.